Felids and spatial interactions with roads: road-kill, corridors, and space use in Brazil - Cerqueira, Rafaela Cobuci (2020)
Roads are among the most important threats for wildlife, mainly because they are ubiquitous sources of mortality, habitat loss and fragmentation. Almost all felid species in Brazil are listed as Vulnerable nationally, and some studies report they are particularly vulnerable to the negative effects of roads. In this study, we used two approaches to assess how six out of the ten species of felids that occur in Brazil spatially interact with roads. In the first manuscript, we compared the outputs of two methods commonly used to identify road segments for mitigation, namely, potential movement corridor models and road-kill likelihood models. We applied circuit theory to identify road segments that cross potential movement corridors and maximum entropy to identify road segments of high road-kill likelihood for five species: northern and southern tiger cats Leopardus guttulus and L. tigrinus, ocelot L. pardalis, jaguarundi Herpailurus yagouaroundi, and puma Puma concolor. We found that movement corridors and high road-kill likelihood do not occur in the same road segments and we suggest that the two methods should be used in a complementary way when prioritizing road segments for mitigation. In the second manuscript, we used structural equation modelling to evaluate direct and indirect effects of roads on space use by jaguars Panthera onca in Brazil. The results showed that space use by jaguars is not directly influenced by roads, but that roads influence space use indirectly through their effects on land-cover. Paved and unpaved roads reduce the amount of natural habitat and favour urban areas, which in reduce the occurrence of jaguars. We argue that indirect effects of roads are subtle and should not be underestimated, especially considering threatened species living in a landscape where there are continuous plans for road network expansion. The third manuscript is a compilation of geo-referenced road-kill data in Brazil, in which I share authorship.